Mining Affairs in The Hand of Local Government: A Case Study of People’s Mining in Muara Enim Regency, Indonesia) - Sena Putra Prabujaya; Bambang Supriyono; M.R. Khairul Muluk; Sujarwoto Sujarwoto (Sekolah Pascasarjana Universitas Brawijaya, 2022)
This study aimed to describe case study of people’s mining in Muara Enim Regency, South Sumatera, Indonesia. This was a case study research with descriptive method to explain the decentralization in mining affair located in Muara Enim regency. Data were collected from resources in the form of documents, archives, and phenomena whilst secondary data were collected from academic articles, Youtube, and online news. The positive impact of decentralization in people’s mining in Muara Enim Regency can be seen in economical aspect. Whereas the negative impact of decentralization in people’s mining are wider in three aspects, namely social, environmental, and human safety aspects. Government revisiting the mining regulations is needed to avoid further conflicts. Research on the key parameter on why a nation should do decentralization is still debated. The implementation of asymmetric decentralization in Indonesia since the new order era until after reform era brings an impact on how the quality of local governance may affect the result. While research on asymmetric decentralization has developed very significantly, only limited attention has been paid to the determinants of success, especially the role governance plays.